Dynamics of the Professional Endurance Indicators in Officers of the Operational Level in a Higher Military Educational Institution During Training - Oleniev, Dmytro G.; Petrachkov, Oleksandr V.; Verbyn, Nazarii B.; Shemchuk, Vadym A.; Tiazhyna, Anzhela M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The paper presents the results of an experimental study on the development of professional endurance and psycho-emotional stability in the future officers of operational level during training in a higher military educational institution. The educational research was conducted in three stages, in the National Defence University of Ukraine, named after Ivan Cherniakhovskyi. The current level of professional endurance in this category of officers gave grounds to assume that with traditional approaches to the organisation of the educational process, it is quite difficult to achieve a high level of development of this property. Therefore, there is a need to find and substantiate the pedagogical conditions for developing professional endurance in officers and improving their mental health. To confirm the effectiveness of the implementation of the conditions defined by the authors at the beginning and end of the experiment, a comparison of the obtained data of the experimental group (EG) and control group (CG) was carried out according to the authors’ criteria and indicators. The results of the study on the implementation and substantiation of pedagogical conditions for the development of professional endurance in officers confirmed that the proposed measures contributed to the effective development of this quality. Statistical methods ensure that the officers from the EG had statistically significant changes in professional endurance as a result of the experiment. Comparison of the development of professional endurance in the EG at the beginning and end of the experiment using the Wilcoxon rank-sum test confirmed the effectiveness of implementing appropriate pedagogical conditions for the development of professional endurance and psycho-emotional stability.